EVOLUÇÃO DA PROBLEMÁTICA DOS SISTEMAS DE CUSTEIO, EM RELAÇÃO ÀS MUDANÇAS DOS CRITÉRIOS DE COMPETITIVIDADE DO AMBIENTE INDUSTRIAL - V. Melo, Ivan; Bornia, Antonio Cezar; A. Menezes, Emílio (Anais do Congresso Brasileiro de Custos - ABC)
Industrial environment changes stress competitiveness criteria associated with Productivity, Quality, Flexibility, Innovation and Environmental Ecology, forcing new management skills and tools adaptation to that reality. Therefore, Cost Management Systems problematic are changing influenced by those competivive dimentions which push cost systems concepption in order to create a proactive industrial management.